Science Applied in Agricultural Modernization and Poverty in Suburban Villages - Amruddin (Jurnal Penelitian Pendidikan IPA, 2025)
Objective study This study examines agricultural modernization and poverty inperi-urban villages. The method used is qualitative, with a study field. As for participants in the study, this is one government official at the Makassar Agriculture Service. And a farmer in a village on the outskirts of Makassar City. Results study This conclude Agricultural modernization in suburban villages, especially around Makassar, has a very important impact on community welfare and economic growth in the region. The government, both at the provincial, city, and district levels, shows a commitment to supporting agriculture as the backbone of providing for the basic needs of citizens. Agricultural modernization, which involves the application of technology, skills training, and supportive policies, is the main solution to overcoming agricultural challenges in peri-urban villages.